The Changing Structure of Japanese Trade Flows : The Changing Structure of Japanese Trade Flows. (IMF Working Papers; Working Paper, 1990)
The changes to the structure of Japanese exports and imports in the second half of the 1980s departed significantly from past trends. Econometric analysis confirms that some of the structural changes-notably the importance of consumer goods trade-cannot be fully explained using conventional trade equations. However, the structural changes were consistent with the likely nonlinear effects of the unusually large appreciation of the yen during 1985-87, which, among other things, precipitated a surge in Japanese foreign direct investment.